Chitosan From Haruan (Channa Striata) Fish Scale Accelerate Wound Healing By Promoting Angiogenesis And Fibroblast Proliferation - Putri, Deby Kania Tri; Fitriyana, Annisa; Raudah, Siti; Wardhana, Agung Satria; Wydiamala, Erida; Sarifah, Norlaila; Budipramana, Melisa (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Damage to the integrity of some body tissues due to trauma commonly referred to as injury can occur intentionally or unintentionally. Angiogenesis and fibroblast proliferation are important stages in the proliferation stage in determining the success of the wound healing process. Chitosan from haruan fish scales has active functional groups in the form of anti-inflammatory and antioxidants that are effective in accelerating wound healing. Method: This study was a pure experimental study with a post-test only design with a control group design which was divided into a treatment group and a control group. The treatment group consisted of chitosan haruan fish scales at concentrations of 1%, 3%, and 5%. The control group consisted of povidone iodine as a positive control and no treatment as a negative control. All rats were injured on the back and then euthanized on days 3, 5, 7, and 14. Result: The chitosan from haruan fish scales affected the formation of new blood vessels and fibroblasts on day-3, increase the number of new blood vessels on day-5, decrease the number of new blood vessels accompanied by increase the number of fibroblasts on day-7, and also decrease the number of fibroblasts on day-14.Conclusion: 3%, and 5% chitosan from haruan fish scale proved to be effective against angiogenesis and fibroblast proliferation in wound healing.